Recognizing the importance of protein quality in an era of food systems transformation - Pikosky, Matthew A.; Ragalie-Carr, Jean; Miller, Gregory D. (Frontiers in Sustainable Food Systems, 2022)
A transformation of current food systems is needed to nourish the growing global population in more sustainable ways. To support this, some are advocating for a shift to plant-based or -exclusive diets. These recommendations – typically borne out of concerns for the environment – often fail to account for unintended nutritional consequences, which could be particularly pronounced for protein intake. While there is enough protein to meet current global needs, the issue of protein quality is often overlooked and oversimplified. High-quality protein, including from animal source foods (ASF), is needed to meet nutritional demands in low- and middle-income countries (LMIC), particularly among vulnerable population groups. In high-income countries (HIC), protein quality is important for at-risk populations who have higher protein requirements and lower energy and/or protein intakes. Further, as the global population increases, driven primarily by population growth in LMIC, it is possible that protein production will need to increase in HIC to support exports to help feed the global population. The global dialogue and resulting dietary recommendations must therefore become more nuanced to consider the interaction between nutritional value and environmental impact to help better reflect trade-offs across multiple domains of sustainability. Nutritional life cycle assessments are one way to help accomplish this nuance and evaluate how all types of food production systems should be refocused to improve their environmental efficiency and nutritional impact.